Reviewing Disasters: Hospital Evacuations in the United States from 2000 to 2017. Issue Volume 34:Issue s1(2019) (May 2019) - Sharma, Aishwarya; Mace, Sharon
Abstract : Introduction: Between 2000 to 2017, there were over 150 hospital evacuations in the United States. Data received from approximately 35 states were primarily concentrated in California, Florida, and Texas. This analysis will provide disaster planners and administrators statistics on hazards that cause disruptions to hospital facilities. Aim: The aim of this study is to investigate US hospital evacuations by compiling the data into external, internal, and man-made disasters thus creating a risk assessment for disaster planning. Methods: Hospital reports were retrieved from LexisNexis, Google, and PubMed databases and categorized according to evacuees, duration, location, and type. These incidents were grouped into three classifications: external, internal, and man-made. Both partial and full evacuations were included in the study design. Results: There were a total of 154 reported evacuations in the United States. 110 (71%) were due to external threats, followed by 24 (16%) man-made threats, and 20 (13%) internal threats. Assessing the external causes, 60 (55%) were attributed to hurricanes, 21 (19%) to wildfires, and 8 (7%) to storms. From the internal threats, 8 (40%) were attributed to hospital fires and 4 (20%) chemical fumes. From the man-made threats, 6 (40%) were attributed to bomb threats and 4 (27%) gunmen. From the 20 total reported durations of evacuations, 9 (45%) lasted between 2 to 11:59 hours, 6 (30%) lasted over 24 hours, and 5 (25%) lasted up to 1:59 hours. Discussion: Over 70% of hospital evacuations in the US were due to natural disasters. Compared to 1971-1999, there was an increase in internal and man-made threats. Exact statistics on evacuees, durations, injuries, and mortality rates were unascertainable due to a lack of reporting. It is critical to implement a national registry to report specifics on incidences of evacuations to further assist with disaster and infrastructure planning.